KUYPER, A. Mulheres da bíblia. Trad. Brian Gordon Kibuuka. Londrina: Penkal/Livraria Família Cristã, 2021. - Vale, Rony Petterson Gomes do; Villar Aparecida, Viviane (Sacrilegens, 2025)
Não se aplica. Resenha.